Address on the opening Alexander von Humboldt Season in Quito, Ecuador, on 13 February 2019 (With an introduction by Ottmar Ette) (HiN - Alexander von Humboldt im Netz. Revue internationale d'études humboldtiennes, 2019)
No abstract available.